Gereja sebagai “Casta Meretrix” menurut Hans Urs von Balthasar - Gabriel, Vincentius; Kristiyanto, Antonius Eddy; Atawolo, Andreas Bernadinus (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
Abstract. The holiness of the Church, in the Scripture and magisterium, could be explained in its depiction as the bride of Christ. With the same depiction, Hans Urs von Balthasar was observantly concerned with the sins of the Church as summarized in his essay, “Casta Meretrix.” This research is a literature study with a historical-critical approach, seeking to explore Balthasar's perspective and its novelty. The study found a new angle offered by Balthasar in understanding the reality of the sinful Church, which centered on the figure and saving action of Jesus Christ, the Bridegroom. Balthasar's view influenced the renewal of the Church in real life, especially during the pontificate of Pope John Paul II. The Church confessed and asked for forgiveness for sins that have been committed as the way of the cross. Finally, we offer two antinomies to understand the nature of the Church. At the same time, the Church: is made up of sinners, but is always called to holiness; and she is historical on earth, but seeks her holiness in union with God in heaven.Abstrak. Kodrat Gereja yang kudus, dalam Kitab Suci dan ajaran resmi Gereja, dapat dijelaskan dalam penggambarannya sebagai mempelai Kristus. Dengan penggambaran yang sama, secara jeli Hans Urs von Balthasar menaruh perhatian pada dosa-dosa Gereja sebagaimana terangkum dalam esainya, “Casta Meretrix.” Kajian ini, dengan metode studi pustaka dan pendekatan historis-kritis, berusaha menggali pandangan Balthasar beserta kebaruannya. Studi ini menemukan cara pandang baru yang ditawarkan Balthasar dalam memahami realitas Gereja yang berdosa, yakni berfokus pada figur dan tindakan penyelamatan Yesus Kristus, Sang Pengantin Laki-laki. Pandangan Balthasar berpengaruh pada pembaruan Gereja secara real, secara khusus pada masa pontifikat Paus Yohanes Paulus II. Gereja melakukan pengakuan dan permohonan pengampunan atas dosa-dosa yang pernah dilakukan sebagai sebuah jalan salib. Akhirnya, kami menawarkan dua antinomi untuk memahami kodrat Gereja. Pada saat bersamaan Gereja: terdiri atas orang-orang berdosa, tetapi selalu dipanggil menuju kekudusan; dan ia menyejarah di dunia, tetapi berusaha mengusahakan kesuciannya dalam kesatuan dengan Allah di surga.